APPLICATION OF ARTIFICIAL NEURAL NETWORKS IN AUTOMATION SYSTEMS - Bektemіr Almas Tanatuly; Julayeva Zhazira Tulegenovna; Karatayeva Zhanbubi Yerzhanovna (Theoretical Hypotheses and Empirical Results, 2025)
Today, the use of artificial neural networks (ANNs) in automation systems is one of the key directions for improving the efficiency of production and management processes. ANNs enable modeling of complex processes, fault detection, and data-driven decision-making. This article discusses the theoretical foundations of neural networks, their role, and applications in automation systems. Examples from industry, energy, and transportation are provided, along with an analysis of advantages and limitations. The study results demonstrate the great potential for the development of AI-based automation systems in the context of Industry 4.0.